THE PLANNING AND DEVELOPMENT OF ECOTOURISM IN UZBEKISTAN USING INTERNATIONAL METHODS - Khayrullaeva, Nilufarbegim (University Research Base, 2024)
The development of ecotourism in Uzbekistan, utilising international methodologies, not only presents an opportunity to promote sustainable tourism but also holds the potential to contribute significantly to the preservation of natural and cultural resources. With its rich biodiversity and historical sites, Uzbekistan can create a balanced tourism approach that supports economic development and environmental conservation by adopting international ecotourism models and integrating local participation. This potential offers a hopeful outlook for sustainable tourism in Uzbekistan.